2013
DOI: 10.1095/biolreprod.112.101873
|View full text |Cite
|
Sign up to set email alerts
|

Glucose-Regulated Protein, 78-Kilodalton Is a Modulator of Luteinizing Hormone Receptor Expression in Luteinizing Granulosa Cells in Rats1

Abstract: Glucose-regulated protein, 78-kilodalton (GRP78) is a molecular chaperone that exists in the endoplasmic reticulum and is involved in the assembly, transportation, and folding of proteins. Previously, GRP78 was reported to associate with gonadotropin receptors. However, little is known about how GRP78 is involved in the regulation of luteinizing hormone receptor (LHR). Thus, in this study, we investigated the significance of GRP78 for the induction of LHR in rat luteinizing granulosa cells. Western blot analys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 35 publications
0
17
0
Order By: Relevance
“…In the present study, mRNA expressions of aat and afp at g55 and grp78 and gen at g90 were decreased in the HFD group compared to the CON group. Early studies also found that these homeostasis-related genes’ mRNA expression is relatively concordant in ovary with proteins [35,36]. Our previous study has confirmed that aat and afp might promote primordial follicles formation, and grp78 and gen could protect primordial follicles from transforming to primary follicles [37].…”
Section: Discussionmentioning
confidence: 54%
“…In the present study, mRNA expressions of aat and afp at g55 and grp78 and gen at g90 were decreased in the HFD group compared to the CON group. Early studies also found that these homeostasis-related genes’ mRNA expression is relatively concordant in ovary with proteins [35,36]. Our previous study has confirmed that aat and afp might promote primordial follicles formation, and grp78 and gen could protect primordial follicles from transforming to primary follicles [37].…”
Section: Discussionmentioning
confidence: 54%
“…Previous studies have suggested that ER stress is involved in a series of reproductive physiological processes in mammals. For example, decreased ER stress is beneficial to increased placental growth (6), and ER stress mediated by GRP78 is essential for corpus luteum formation and for maintaining normal secretory functions (20). As a crucial player in the ER stress signaling pathway, ATF6 is present in the extravillous trophoblasts, myoblasts, and cartilage (24,30), and the expression of ATF6 in various cells and tissues implies that it may play different roles in different physiological processes.…”
Section: Discussionmentioning
confidence: 99%
“…For example, overexpression of glucose-regulated protein 78 (GRP78), a heat shock protein upregulated during ER stress, in HEK-293 cells stably expressing FSHR, leads to decreased FSHR protein. 79 We observed an at least 20-fold increase in Grp78 levels in ER stress-induced GCs (data not shown), which could lead to decreased FSHR levels and decreased FSH response.…”
Section: Discussionmentioning
confidence: 72%